Unravelling settlement history at Ndondondwane, South Africa: a micro-chronological approach - Fowler, K. D.; Greenfield, H. J. (Southern African Humanities, 2009)
The ability to conduct high (micro-) resolution spatial-temporal analysis of deposits at Iron Age sites is a significant problem in southern African archaeology. The consequence is that temporal analyses are therefore rarely conducted at a finer level than the ceramic phase within a larger period (e.g. Early Iron Age). This leads to the common practice of comparing all deposits at sites from the same phase as if they were contemporaneous. One potential solution to this problem involves integrating ceramic, stratigraphic, and chronometric data. In this paper, we use radiocarbon, stratigraphic, and ceramic stylistic data to identify a pan-site chronological sequence for the Early Iron Age site of Ndondondwane. This is achieved by synchronizing the superimposed stratigraphic sequence and associated radiocarbon data from the centre of the site with evidence for micro-temporal changes in ceramic style. The micro-temporal stylistic changes allow the correlation of stratigraphically displaced and spatially isolated deposits across the site into a pan-site chronological sequence. The combination of all three data sets increases the ability of archaeologists to detect change at smaller temporal scales that are normally conflated into a single-period occupation.